(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
A reversed phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the simultaneous determination of losartan potassium, naproxen and pioglitazone hydrochloride. Chromatographic separation was performed on a Phenomenex Gemini C18 column (250 x 4.6 mm, 5 µm) with a mobile phase of acetonitrile: 2% acetic acid in water (60:40, v/v) at a flow rate of 0.7 mL/min. Detection was performed at 230 nm using a UV detector. Under the optimized conditions, the retention times for losartan potassium, naproxen and pioglitazone hydrochloride were 6.24, 8.34 and 14.86 minutes, respectively, with well-resolved and symmetrical chromatographic peaks. The method showed good linearity within the concentration range of 40-60 µg/mL for all analytes, with correlation coefficients greater than 0.998. Precision studies showed low %RSD values for both intra-day (0.01-0.79%) and inter-day (0.08-0.85%) analyses. Accuracy was evaluated through recovery studies, with intra-day recoveries ranging from 99.31-101.74% and inter-day recoveries ranging from 99.83-101.56%. Robustness testing confirmed that small variations in chromatographic conditions did not influence the analytical performance. The method was validated according to ICH Q2(R1) guidelines and demonstrated excellent linearity, precision, accuracy and robustness. Therefore, the developed RP-HPLC method is suitable for simultaneous quantitative analysis of these drugs. Dhaka Univ. J. Pharm. Sci. 25(1): 55-63, 2026 (June)